Recent Advances on the Design and Applications of Antimicrobial Nanomaterials - Clara Ortega-Nieto; Noelia Losada-Garcia; Doina Prodan; Gabriel Furtos; Jose M. Palomo (Nanomaterials, 2023)
Present worldwide difficulties in healthcare and the environment have motivated the investigation and research of novel materials in an effort to find novel techniques to address the current challenges and requirements. In particular, the use of nanomaterials has demonstrated a significant promise in the fight against bacterial infections and the problem of antibiotic resistance. Metal nanoparticles and carbon-based nanomaterials in particular have been highlighted for their exceptional abilities to inhibit many types of bacteria and pathogens. In order for these materials to be as effective as possible, synthetic techniques are crucial. Therefore, in this review article, we highlight some recent developments in the design and synthesis of various nanomaterials, including metal nanoparticles (e.g., Ag, Zn, or Cu), metal hybrid nanomaterials, and the synthesis of multi-metallic hybrid nanostructured materials. Following that, examples of these materials’ applications in antimicrobial performance targeted at eradicating multi-drug resistant bacteria, material protection such as microbiologically influenced corrosion (MIC), or additives in construction materials have been described.